Perceptions and intentions of adopting the Internet of Things by Generation Z - Gonçalves, Silvana Costa (2020)
The Internet of Things (IoT) represents a new technological revolution expected to impact all aspects of our daily lives in the future. Generation Z is foreseen as playing a fundamental role in the adoption of this type of technology, namely because of their growing importance as a consumer segment, their global role in the society, and in particular their close relationship with technology. However, extant literature on the adoption of IoT disregarded this segment. This paper aims to fulfill this gap, by exploring their knowledge, perceptions, and intentions of adopting IoT. After considering the main contributions in the consumer behavior literature regarding IoT, a qualitative approach was adopted, and 7 semi-structured interviews were conducted with Portuguese consumers aged 18-22. Content analysis was performed following the recommendations by Bardin (1977). The results showed that although Generation Z is not familiar with the concept of the IoT, they expressed a strong desire to integrate IoT technology in their lives, being open to its adoption in all fields of application, including for personal use, at home, and for work. One of the conclusions is that in order to foster the IoT adoption by this Generation, the functional benefits (performance, price, comfort, and safety) should be emphasized, so that the main risks perceived are weakened, namely the financial, performance, and physical risks.